Processos de subjetivação de pessoas vivendo com HIV/AIDS : considerações acerca de um grupo de adesão ao tratamento - Santos, Elder Magno Freitas (2012)
The AIDS epidemic turns 30 years since its release in early 1980. Since then, models have emerged to fight the epidemic and responses to its spread and a social imaginary and psychic marked by the figures of death, the blame and stigmatization of people affected by the disease. In this situation, other practices organized reinforced by the dynamics of the epidemic, social mobilization and the emergence of antiretroviral therapies, indicating the necessity of considering a specific system of care for people living with HIV / AIDS (PLWHA) that goes beyond of disease. Such reformulations can be condensed in the concept of "health promotion" which is an expanded look at the health care policy toward PLHA synthesized by notions of empowerment and vulnerability. So, this research aims to understand subjectivation processes of PLWHA in the context of a "group of treatment adherence" in the city of Aracaju, from the clash between their narratives, the imaginary about AIDS and the institutional discourses. The analysis discourses of group membership and the PLWHA showed the dual importance of the problems and the consolidation of policy for health promotion AIDS, to the extent that it falls models of intelligibility of the disease and society marked by control and safety devices associated with the modern discourse of prevention. In this sense, ways of thinking about health care policy and psychological clinic itself may reproduce processes of subjection about the guilt, victimization and political exploitation that holds the place of AIDS as a disease of the others to be governed. But at the same time, the membership group" indicates their affective and critical power, that resists constraints in the name of a common, for does not fall into an identity logical, the friendship.